Analisis Dampak Implementasi Konsep Smart City terhadap Ekologi Perkotaan dan Kualitas Hidup Masyarakat dalam Perspektif Lingkungan dan Keberlanjutan Jangka Panjang - Mia Kusmiati; Andi Ningrat (Journal of New Trends in Sciences, 2023)
The concept of the smart city has emerged as a strategic response to rapid urbanization, increasing population density, and escalating environmental degradation. It is designed to create more efficient urban management through the integration of information and communication technologies, with the primary goal of enhancing public services, optimizing resource use, and improving citizens’ quality of life. One of its most significant promises is its potential to mitigate ecological challenges, particularly in monitoring and reducing air pollution levels. This study aims to analyze the impact of smart city implementation on urban ecology and quality of life, focusing on air quality as a key indicator. A quantitative comparative approach was applied, using both primary data from air quality measurements PM2.5, CO₂, NO₂, and AQI and secondary data from government reports, environmental agencies, and academic publications. The research was conducted in five major Asian cities recognized for adopting smart city initiatives. The results reveal varied outcomes: Tokyo and Kuala Lumpur demonstrated substantial improvements in air quality and livability, while Beijing and New Delhi continued to struggle with severe pollution. Jakarta showed partial progress, though improvements remain limited. These findings indicate that while technology is critical, it alone does not ensure ecological sustainability. Effective governance, public participation, and context-based strategies are equally crucial. This study highlights the need for smart city policies to prioritize ecological resilience and human well-being as central elements of sustainable urban development.